Transcription factor Sox10 regulates oligodendroglial Sox9 levels via microRNAs. Issue 7 (3rd April 2017) - Reiprich, Simone; Cantone, Martina; Weider, Matthias; Baroti, Tina; Wittstatt, Jan; Schmitt, Christian; Küspert, Melanie; Vera, Julio; Wegner, Michael
Abstract: During development of myelin‐forming oligodendrocytes in the central nervous system the two closely related transcription factors Sox9 and Sox10 play essential roles that are partly shared and partly unique. Whereas Sox9 primarily functions during oligodendroglial specification, Sox10 is uniquely required to induce terminal differentiation and myelination. During this process, Sox10 protein levels rise substantially. As this coincides with a reciprocal decrease in Sox9, we postulated that Sox10 influences Sox9 amounts in differentiating oligodendrocytes. Here we show that Sox9 levels are indeed inversely coupled to Sox10 levels such that Sox10 deletion in oligodendroglial cells evokes a reciprocal increase in Sox9. We furthermore provide evidence that this coupling involves upregulation of microRNAs miR335 and miR338 as direct transcriptional targets of Sox10. The two microRNAs in turn recognize the 3′‐UTR of Sox9 mRNA and may thereby reduce Sox9 protein levels posttranscriptionally in oligodendroglial cells. Such a mechanism may enable oligodendroglial cells to adapt the ratio of both related Sox proteins in a manner required for successful lineage progression and differentiation. Mathematical modeling furthermore shows that the identified regulatory circuit has the potential to convert a transient stimulus into an irreversible switch of cellular properties and may thus contribute to terminal differentiation of oligodendrocytes. Main Points: Oligodendroglial Sox9 expression is inversely coupled to Sox10 via microRNAs. Sox10 stimulates oligodendroglial expression of miR335 and miR338. MiR335 and miR338 target Sox9.